A rede de atenção a população em situação de rua: possibilidades de interferência na definição e concretização de uma política pública na cidade de São Paulo - Amaral, Denise Perroud (2010)
The need of solving the complexity of the social reality of the population in street situation of the city of São Paulo has been mobilizing several social actors in networks, especially social organizations and movements since the 90s. These actors intend to discuss and accomplish a public policy aiming at this population and at the organization of socio-assistance services for their necessities. The objective of this research was to identify the existing arrangements related to the social actors who compose the so-called Attention Network for Populations in Street Situation in the central area of the city of São Paulo. The theme of the social networks has allowed a theoretical approach to the analyses of authors such as Castells (1999), Marques (1999, 2006), Junqueira (2000, 2002, and 2004), Rico and Raichelis (1999), Quandt and Souza (2008), Mizruchi (2006), and Scherer-Warren (1996). The use of a qualitative approach, including analysis of the content of semi-structured interviews, Snowball pattern methods, and Sociometrics, allowed to identify the relations that the actors establish among themselves, in the collective spaces, and also with the Secretaria Municipal de Assistência e Desenvolvimento Social. It was also possible to identify the intensity of these relations and the perception that the actors have of their capacity of influencing the accomplishment of the national public policy. The study revealed the network of socio-assistance character of the society, notably in the case of traditional organizations of religious aspect which are articulated in a political network with public authorities through the establishment of conventions. The network which was studied here presented two central triads or subgroups: one under the influence of the Permanent Forum for the Assistance of Public Policies of Populations in Street Situation of São Paulo, and the other under the influence of the Network for the Socio-Assistance Attendance of SMADS. The first triad was notable for the intensity of the relations established through contacts in a daily basis, and for the capacity of articulating different actors to influence on the definition of a national public policy dedicated to this population. The intermediation that connects these two triads achieved by only one social organization avoided the constitution of two isolated subgroups with different objectives